Air pollution and adult cognition - La Nauze, Andrea (2025)
Funding Information: Andrea La Nauze is at Deakin University ( a.lanauze@deakin.edu.au ). Edson Severnini is at Boston College, Nova School of Business and Economics, National Bureau of Economic Research (NBER), and Institute of Labor Economics (IZA) ( edsons@andrew.cmu.edu ). We thank our editor (Daniel Millimet), anonymous reviewers, Karen Clay, Jonathan Colmer, Tatyana Deryugina, Nick Kuminoff, Paulina Oliva, Nick Sanders, seminar participants at the Australian National University, Carnegie Mellon University, Cornell University, Lumos Labs, Inc., and the University of Adelaide, and conference participants at the eighth IZA workshop: Environment, Health and Labor Markets for invaluable comments and suggestions. We gratefully acknowledge financial support from the University of Pittsburgh and the Heinz College at Carnegie Mellon University. Declarations of interest: none. Publisher Copyright: © 2024 The Association of Environmental and Resource Economists. All rights reserved.